Phosphorus metabolism in chronic kidney disease - Fourtounas, C (LITHOGRAPHIA Antoniadis I.-Psarras Th. G.P., 2011)
The knowledge about the exact mechanisms involved in phosphorus homeostasis and the evolution of secondary hyperparathyroidism in chronic kidney disease (CKD) has improved during the last years. The discovery of Fibroblast Growth Factor 23 (FGF23) has revolutionized our understanding about the links between mineral metabolism, vitamin D and parathyroid hormone (PTH). FGF23 serum levels increase early in CKD before the increase of serum phosphorus or the decrease of vitamin D and there is parathyroid resistance to FGF23 in advanced CKD. Increased levels of serum phosphorus have been related in epidemiological studies with adverse outcomes in patients with CKD, diabetes, coronary artery disease, or even normal adults. In patients with CKD stage 3 or 4, low phosphorus diets have been related with adverse outcomes due to the risk of malnutrition and there are limited data regarding the role of phosphate binders in these patients. Recent studies suggest that increased serum FGF23 levels are associated with mortality, left ventricular hypertrophy and progression of CKD independently of serum phosphorus levels. There is an ongoing debate about the "normal" or "desirable" levels of serum phosphorus in CKD and a new role of FGF23 as a marker of the disturbances of mineral metabolism in CKD is emerging.